2021
DOI: 10.1007/s11356-021-14373-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on cereal production: evidence from lower-middle-income countries

Abstract: This study empirically examines the impact of climate change on cereal production in selected lower-middle-income countries with a balanced panel dataset spanning the period 1971-2016. The study uses average annual temperature, average annual rainfall, and CO 2 emissions to measure climate change. Besides this, cultivated land under cereal production, and rural population are also used as the control variables. Second generation unit root tests, i.e., CIPS, and CADF, are used to test the stationarity of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 81 publications
9
47
1
Order By: Relevance
“…The coefficient of rainfall is showing a negative impact on rice productivity at 10% level. It is contradicting to various studies which have shown a positive effect of increased rainfall on agricultural productivity (Kumar et al, 2021). Further, the negative impact can be observed due to an increase in rainfall during the ripening stage (Abbas & Mayo, 2021).…”
Section: Insert [Table 8]contrasting
confidence: 66%
See 2 more Smart Citations
“…The coefficient of rainfall is showing a negative impact on rice productivity at 10% level. It is contradicting to various studies which have shown a positive effect of increased rainfall on agricultural productivity (Kumar et al, 2021). Further, the negative impact can be observed due to an increase in rainfall during the ripening stage (Abbas & Mayo, 2021).…”
Section: Insert [Table 8]contrasting
confidence: 66%
“…Asian country-based studies (Praveen & Sharma, 2019;Baig et al, 2020;Janjua et al, 2014;Ahsan et al, 2020) and Punjab region-specific studies (Grover & Upadhyay, 2014;Hundal & Kaur, 2007;Kumar & Sidana, 2019;Mahmood et al, 2012) have shown that rainfall and temperature are affecting rice, wheat and other crops positively and negatively depending upon when the extreme or scarce rainfall is received, variation in maximum and minimum temperature. Kumar et al (2021), Kumar & Sidana (2019); Appiah et al (2018); Zaied & Zouabi (2015) have looked into all of the concerns, including serial correlation, panel group-wise heteroscedasticity, and cross-sectional dependence. But there is a notable paucity of empirical research focusing specifically on analysing the impact of changing climate pattern on most cultivated crops in Punjab, i.e., wheat and rice.…”
Section: Insert [Table 1]mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, carbon emissions increase each year. Kumar, P. et al indicated a positive relationship between carbon emissions and cereal production [40]; Pickson, R. B et al stated that CO 2 emissions have a significant negative impact on cereal production in the long run [30] and show a unidirectional causality and Ahsan F et al had the same conclusion as Pickson, R. B et al on the relationship between cereal production and CO 2 emissions, but their study showed a bidirectional causal relationship between CO 2 emissions and cereal production [35]. These findings are not the same as the relationship between bean yields and CO 2 emissions in this paper, but this does not mean that it has no effect on the growth of bean crops in China.…”
Section: Discussionmentioning
confidence: 99%
“…It provides raw materials for industrial use for hastening up industrialization. Agriculture involves crops production, forestry, livestock husbandry, fishery, man's use and consumption, and processing and marketing of its products (Nesheim et al 2015;Kanianska 2016;Kumar et al 2021a). Moreover, it creates ample employment opportunities for unskilled or rural landless workers, which help poverty alleviation and improve the overall social well-being of the people (Pingali et al 2019).…”
Section: Introductionmentioning
confidence: 99%